Carbon nanotube entangled Mn3O4 octahedron as anode materials for lithium-ion batteries. (30th May 2017) - Cui, Xia; Wang, Yuqiao; Xu, Qingyu; Sun, Pingping; Wang, Xiuzhen; Wei, Tao; Sun, Yueming
Abstract: A nanocomposite of Mn3 O4 octahedrons entangled by carbon nanotubes (CNTs) was synthesized by a hydrothermal method assisted with a non-ionic surfactant. The integration of octahedral structure and CNTs could offer many critical features, which are needed for high activity anodes, such as fast ion diffusion, good electronic conductivity, and skeleton supporting function, thus enabling the nanocomposite-based anodes with excellent electrochemical performance. In addition, CNTs can not only serve as the conductive network and structure skeleton to improve the anode performance, but also play an indispensable role in the formation of more uniform Mn3 O4 octahedrons. The lithium-ion batteries based on the CNTs-entangled Mn3 O4 octahedrons delivered a high capacity of over 800 mAh g −1 at a current density of 0.2 C for 200 cycles, and even as high as 678.4 mAh g −1 when cycled at 0.5 C after 400 cycles, exhibiting a high capability and ultralong cycle life.